2019
DOI: 10.3748/wjg.v25.i23.2898
|View full text |Cite
|
Sign up to set email alerts
|

NIMA related kinase 2 promotes gastric cancer cell proliferationviaERK/MAPK signaling

Abstract: BACKGROUND NIMA related kinase 2 (NEK2) is closely related to mitosis, and it is currently considered to be over-expressed frequently in many poorly prognostic cancers. However, the effect of the up-regulated NEK2 on cellular signaling in tumors, such as gastric cancer (GC), is con-fusing. AIM To determine the role of the up-regulation of NEK2 in GC. METHODS To investigate the pathological significance of NEK2 in GC, the expression pattern of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…NEK2 has been reported to function as an oncogene in diverse cancers, and it exhibits an intimate correlation with the drug resistance of tumors. In hepatocellular carcinoma (HCC), for example, NEK2 activates the transcription of downstream target genes through stabilizing β-catenin and promoting its translocation to the nucleus, consequently enhancing the sorafenib resistance in HCC cells (Deng et al, 2019). reported that NEK2 potentiated the malignant proliferation of gastric cancer cells via the ERK/MAPK axis.…”
Section: Discussionmentioning
confidence: 99%
“…NEK2 has been reported to function as an oncogene in diverse cancers, and it exhibits an intimate correlation with the drug resistance of tumors. In hepatocellular carcinoma (HCC), for example, NEK2 activates the transcription of downstream target genes through stabilizing β-catenin and promoting its translocation to the nucleus, consequently enhancing the sorafenib resistance in HCC cells (Deng et al, 2019). reported that NEK2 potentiated the malignant proliferation of gastric cancer cells via the ERK/MAPK axis.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with our observation, it was previously demonstrated that NEK2 silencing decreases proliferation and induces apoptosis in CRC cells 18 and that NEK2 regulates Wnt/β-catenin signaling pathway which plays a pivotal role in exerting cancer stemness 14 , 19 . It was also found that ERK is functionally associated with NEK2 expression and knockdown of NEK2 inhibits ERK phosphorylation in gastric cancer cells 20 . Western blotting validated that silencing of RPL17 expression reduces the levels of NEK2/β-catenin and the activity of ERK in both HCT116 and HT29 cells (Fig.…”
Section: Resultsmentioning
confidence: 97%
“…These data indicate that although RPL17 is involved in protein synthesis, it does not affect entire cellular protein biosynthesis, it is rather gene-specific and protein-specific. Of all the genes that were dysregulated by RPL17 knockdown, oncogenic NEK2, which is known to regulate ERK phosphorylation for cell survival 20 , was down-regulated in network 2 of the IPA (Fig. 7 C).…”
Section: Discussionmentioning
confidence: 99%
“…However, data from other cancers indicate that NEK2 and PIM1 kinases possess oncogenic potential and that they interact with diverse downstream signaling pathways. In vitro studies have shown that NEK2 promotes cell proliferation by AKT and Wnt activation in NSCLC [ 45 ] and hepatocellular carcinoma [ 46 ] and via ERK/MAPK (extracellular signal-regulated kinase/mitogen-activated protein kinase) signaling in gastric cancer [ 47 ]. Moreover, NEK2 deregulation was found to act as drivers of tumorigenesis in breast cancer by induction of centrosome amplification [ 16 ].…”
Section: Discussionmentioning
confidence: 99%